![y\text{ = }(1)/(2)x^2z^2](https://img.qammunity.org/2023/formulas/mathematics/college/wig3svwwxm3adklwzm1lqtpfzwer2t5of8.png)
Step-by-step explanation:
Given:
y varies jointly as the square of x and square of z
Mathematically:
![\begin{gathered} y\text{ }\propto x^2z^2 \\ To\text{ equate the expression:} \\ y\text{ = k}x^2z^2 \\ \text{where k = constant of proportionality} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/v8m55ge3talnv6bx5fxkb320a1dystn8j2.png)
when x = 3 and z = 4, y = 72
We need to find the value of the constant of proportionality, k
Substitute for x, y and z in the equation above:
![\begin{gathered} 72=k(3^2)(4^2) \\ 72\text{ = k(9)(16)} \\ 72\text{ = }144k \\ \\ \text{divide both sides by 144:} \\ (72)/(144)\text{ = }(144k)/(144) \\ k\text{ = 1/2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/i88awfvrwdlsvcgt6ahlmipn9fll5qs7up.png)
The equation showing the relationship between x, y, and z:
![y\text{ = }(1)/(2)x^2z^2](https://img.qammunity.org/2023/formulas/mathematics/college/wig3svwwxm3adklwzm1lqtpfzwer2t5of8.png)